Application of Bowling Game Method to Introduce Numbers in PAUD Nurul Iman - Sari, Novita; Manto, Manto (Innovative: Journal Of Social Science Research, 2024)
Play is an essential activity for children, because play for children has the same value as work and study for adults. This means that play is a means to change children's potential strengths into various abilities in children's lives later. Through play, children get multiple experiences to know the surrounding world. With the stimulation of play, children can also carry out developmental tasks. Playing bowling is a great way to help kids practice counting from one to ten. The goal of this research is to find out how the rules and strategies of bowling games affect the number recognition abilities of PAUD Nurul Iman students. Classroom action research (PTK) is used in two cycles. The findings indicate that the children of PAUD Nurul Iman from Talang Baru Village, Pajar Bulan District, Lahat Regency, were able to improve their number recognition skills through bowling ball training, which was carried out over the course of two cycles of three meetings each. The fact that the capacity to identify numerical symbols improves with each Cycle is evidence of this.